The Factors influence the Students’ Learning Outcome in Translation Subject by Using Android - Refika Andriani; destina kasriyati (ELT-Lectura, 2018)
This research aimed at describing the factors influence the students’ learning outcome in Translation Subject by using Android. This research conducted at the fourth semester of English Department of Education and Teachers Training Faculty of Universitas Lancang Kuning. The sample of this research is 30 % of the total number of the population, they are about 7 students. The method of this research is descriptive analysis. Before getting the data by interviewing the students and observation during teaching and learning process of Translation Subject by using android, they had got a test of translating an English text into bahasa Indonesia. Finally, it is found that there are three factors influence the students learning outcome in translation subject by using android. They are motivated media, learning atmosphere, and easy access.